Innovation theories: relevance and implications for developing country innovation - Andréanne Léger; Sushmita Swaminathan (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Innovation is at the basis of economic development and as such, it is instrumental for developing countries. We review the literature on innovation from the perspectives of four select branches of economics to build a conceptual framework of innovation applicable to developing countries. The conceptual framework includes insights from the surveyed literature and identifies areas of further research. Finally, we conclude with policy recommendations for innovation policies in developing countries highlighting the fact that intellectual property protection is not likely to be at the basis of innovation in these countries.
Keywords: O31; B41; P20; 330; Innovation; Development; Absorptive Capacity; Innovation; Entwicklungstheorie; Theorie; Innovationspolitik; Immaterialgüterrechte; Entwicklungsländer